METODE WATERFALL PENJUALAN MEBEL PROPERTI BERBASIS WEB - Verra Sofica (LPPM UNIVERSITAS BINA INSAN, 2019)
Distance and time are some factors that become a very important consideration for customers in making purchase transactions. Making e-commerce about selling Mabel Property online to make it easy for customers to make purchases, so that customers do not have to bother anymore to come to their destination and can save time and money. In developing this software the writer uses the Waterfall method. The navigation structure used is a mixture. Making code using the PHP programming language and to regulate the appearance of website design using CSS. Data collection using the method of observation and literature study. For testing the web the author uses the black box method. The results of this research are the formation of an online buying and selling website which can handle sales and online ordering.